Experimental analysis of composite repair in the Offshore Industry (Research, Society and Development, 2024)
With the expansion of oil exploration activities using FPSOs (Floating, Production, Storage, and Offloading), alternatives that allow for cost reduction in maintenance without compromising reliability have become essential for business profitability. The use of bonding techniques on vessels, ship hulls, and pipelines stands out as a best practice as it can be carried out on-site, avoiding the risks and disadvantages of hot work and eliminating the need for activity interruption. The objective of this study is to analyze the experimental results of tests conducted on joints made of steel and carbon fiber composite and establish the repair's service life in terms of fatigue cycles. Test specimens were made with the same materials used by PETROBRAS in the field. Static tests were performed to determine the maximum displacement load of the repair, and dynamic tests were conducted with ranges varying every 10% from 50% to 90% of the maximum load to obtain the repair's service life. The results showed that with a load of 90%, displacement occurs in the first few cycles, and with 60% of the maximum load, the specimens began to fail around 105 cycles, qualifying them for use. It is concluded that the use of composite repairs subjected to 60% loads exhibits infinite life and is therefore qualified for use, presenting itself as an alternative for repairs in offshore installations.